2016
DOI: 10.1186/s12889-016-2998-9
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking intentions for early signs of mental illness and their associated factors: comparison across four kinds of health problems

Abstract: BackgroundFailure and delay in initial treatment contact for mental disorders has been recognized as an important public health problem. According to the concept of mental health literacy, recognition of symptoms is crucial to making decisions to seek or not seek professional help. The aims of this study were to investigate the types of health problems for which Japanese adults intend to seek help, their preferred sources of help, and the factors associated with help-seeking intentions.MethodsA cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 54 publications
(81 reference statements)
2
45
1
1
Order By: Relevance
“…Mental health literacy, defined as knowledge and understanding regarding symptoms and treatment of Help-Seeking and Psychological Distress in Japanese Workers mental health issues, was found to be one of the key factors for help-seeking behavior related to mental health issues such as depression. 20,21 The findings of the current study are consistent with previous studies suggesting that younger individuals have better mental health literacy than older persons. Moreover, poor mental health literacy may delay help-seeking.…”
Section: Discussionsupporting
confidence: 91%
“…Mental health literacy, defined as knowledge and understanding regarding symptoms and treatment of Help-Seeking and Psychological Distress in Japanese Workers mental health issues, was found to be one of the key factors for help-seeking behavior related to mental health issues such as depression. 20,21 The findings of the current study are consistent with previous studies suggesting that younger individuals have better mental health literacy than older persons. Moreover, poor mental health literacy may delay help-seeking.…”
Section: Discussionsupporting
confidence: 91%
“…Personal characteristics, social determinant factors, and social/family support have been reported as some of the elements that contribute to the complexity of stroke patients [48]. Because depressive mood leads to a lowered likelihood of help-seeking intention [50], identifying the risk factors of depressive symptoms after a stroke is necessary. This study showed that assessment of risk factors should consider the interactions between gender, economic status, education level, and presence/absence of a spouse.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore mimamori can create a “win-win” community – older people benefit from the community people and the community people benefit from the act of ‘mimamori’ by establishing relationships of mutual trust. Community-based interventions for creating an atmosphere of friendliness and approachability, and facilitating daily interactions with neighbors, is worth considering as a public health strategy for encouraging help-seeking among older people who tend to be socially isolated [48] and community people respectively. If people can enjoy supportive relationships and thus prevent the trend toward social isolation, and if this can spread to rebuilding of relationships across society, older people and entire communities will be able to lead healthier and more agreeable and productive lives.…”
Section: Discussionmentioning
confidence: 99%